Harmonization of International Commercial Law and Personal Data Protection in the Blockchain Era: Challenges and Regulatory Reconstruction in Indonesia - Oktafiani Permata Dewi; M. Mabrur Riyamasey M; Carlos Ricardo M; Farha Azra Z (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2026)
This research examines the urgency of harmonizing international trade law with personal data protection in the blockchain era. The rapid adoption of blockchain technology in global trade transactions presents new legal challenges related to jurisdiction, privacy, and data security. The purpose of this paper is to analyze the legal vacuum in Indonesia regarding data protection within cross-border digital trade and to formulate reconstruction efforts for future regulations that align with international principles. The study employs a normative juridical method with a statutory, conceptual, and comparative approach to examine the synchronization between Indonesian law, international trade conventions, and data protection standards such as the GDPR. The results indicate that Indonesia’s regulatory framework is still fragmented, requiring comprehensive harmonization to ensure legal certainty and international competitiveness. The implication of this research emphasizes the need for a unified regulatory model integrating trade law and data protection to support blockchain-based economic transformation.